2017
DOI: 10.3390/ma10050526
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Cellulose with Succinic Anhydride in TBAA/DMSO Mixed Solvent under Catalyst-Free Conditions

Abstract: Homogeneous modification of cellulose with succinic anhydride was performed using tetrabutylammonium acetate (TBAA)/dimethyl sulfoxide (DMSO) mixed solvent. The molar ratio of succinic anhydride (SA) to free hydroxyl groups in the anhydroglucose units (AGU), TBAA dosage, reaction temperature, and reaction time were investigated. The highest degree of substitution (DS) value of 1.191 was obtained in a 10 wt% TBAA/DMSO mixed solvent at 60 °C for 60 min, and the molar ratio of SA/AGU was 6/1. The molar ratio of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
(76 reference statements)
1
15
0
Order By: Relevance
“…The degree of substitution and carboxyl content increased with the increasing content of TBAA in the binary solvent, which confirmed that more carboxyl groups were grafted onto the CNFs at higher TBAA contents. This result is also in agreement with our previous study on the homogenous modification of cellulose with succinic anhydride in the same reaction medium . Within a certain range, both the solubility and the dissolution rate of cellulose in the TBAA/DMSO mixed solvent increased with increasing TBAA content.…”
Section: Figuresupporting
confidence: 93%
See 3 more Smart Citations
“…The degree of substitution and carboxyl content increased with the increasing content of TBAA in the binary solvent, which confirmed that more carboxyl groups were grafted onto the CNFs at higher TBAA contents. This result is also in agreement with our previous study on the homogenous modification of cellulose with succinic anhydride in the same reaction medium . Within a certain range, both the solubility and the dissolution rate of cellulose in the TBAA/DMSO mixed solvent increased with increasing TBAA content.…”
Section: Figuresupporting
confidence: 93%
“…Within a certain range, both the solubility and the dissolution rate of cellulose in the TBAA/DMSO mixed solvent increased with increasing TBAA content. As a result, the accessibility of modification reagent (i.e., cyclic anhydride) to the hydroxy groups on dissolved cellulose improved, which would increase the DS value of modified cellulose . This mechanism would also apply to the heterogeneous modification of cellulose in the TBAA/DMSO binary solvent, in which the acetate ions formed hydrogen bonds with the hydroxy groups on cellulose and therefore, to some extent, cleaved the intra‐ and intermolecular hydrogen bonds of cellulose chains.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Succinyl group consists of two carbonyl moieties, where it is expected to provide more electronegative sites compared to the carboxymethyl group. In work reported by Xin et al [ 20 ] and Zhu et al [ 11 ], succinyl cellulose and succinyl chitosan were successfully synthesized, respectively. However, the preparation methods were lengthy and tedious.…”
Section: Introductionmentioning
confidence: 99%